Factors influencing tourist loyalty to Nusa Penida during the post-COVID-19 recovery period - I Wayan Suardana; Saroyeni Piartrini; Ni Made Ariani; I Gede Gian Saputra (Journal of Applied Sciences in Travel and Hospitality, 2025)
This study examines the interplay between destination image, social media influencers, and tourist motivation in shaping tourist loyalty during the post-COVID-19 recovery period. Anchored in the context of Nusa Penida—a rapidly emerging coastal ecotourism destination in Bali—this research develops a behavioral loyalty framework relevant to nature-based tourism. Employing a quantitative design, data were collected through a structured online survey administered to 250 international tourists who had previously visited Nusa Penida. Given the unknown population size, quota sampling was applied, and data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. The findings reveal that social media influencers exert the most substantial direct influence on tourist loyalty, followed by the mediating roles of destination image and tourist motivation. These results underscore the significance of digital storytelling, perceived destination quality, and emotional engagement in fostering revisit intentions, particularly among younger, digitally active travelers. Theoretically, this study contributes to the tourism behavior literature by integrating influencer dynamics into a multi-construct loyalty model, which explains 61.3% of the variance in tourist loyalty. Practically, the research offers strategic insights for destination marketers, emphasizing the importance of authentic influencer collaborations and emotionally resonant digital experiences to strengthen destination competitiveness. From a managerial perspective, the findings highlight the necessity of leveraging targeted digital engagement strategies. Future research should explore cross-generational and cross-cultural variations in tourist responses to influencer-driven content, as well as comparative platform effectiveness across different destination typologies.